Nonlinear Structural Dynamics and Damping - Jauregui, Juan Carlos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book compiles recent research in the field of nonlinear dynamics, vibrations and damping applied to engineering structures. It addresses the modeling of nonlinear vibrations in beams, frames and complex mechanical systems, as well as the modeling of damping systems and viscoelastic materials applied to structural dynamics. The book includes several chapters related to solution techniques and signal analysis techniques. Last but not least, it deals with the identification of nonlinear responses applied to condition monitoring systems. .
1. 1 New trends in nonlinear dynamics of structures -- 2 Time-frequency techniques for identifying nonlinear responses -- 3 Non parametric analysis techniques applied to nonlinear dynamics -- 4 Modeling of friction and damping in machinery -- 5 Modelling of nonlinear vibrations of beams and frames -- 6 Nonlinear dynamics of complex mechanical systems -- 7 Measurement of dynamic variables applied to structures and machinery -- 8 Case Studies.
Keywords: Machinery; Nonlinear Optics; Multibody systems; Vibration; Mechanics, Applied; Machinery and Machine Elements; Nonlinear Optics; Multibody Systems and Mechanical Vibrations